Representation of The American Value in Elemental (2023) Film - Hutapea, Christina Pesta; Muhammad Fitratullah (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The 2023 animated film Elemental is more than just a bright depiction of Elemental characters living in a fantasy world; it also represents deeply ingrained American values, particularly those that have shaped contemporary American culture. This article examines how Elemental’s characters and narrative structure reflect Robert Kohls’ key beliefs of individuality, personal success, and equality of opportunity. This research illuminates how American principles are reflected, both overtly and implicitly, in modern animation by closely examining the film’s themes, character development, and symbolic components. The analytical approach combines literary analysis and cultural contextualization to highlight how Elemental not only entertains but also serves as a reflection of American society norms. This study emphasizes the significance of examining media to find the underlying principles that shape cultural products, demonstrating how popular culture can serve as a lens for better understanding society norms and standards.